Sedentarization and maternal childcare networks: role of risk, gender and demography. (16th January 2023) - Page, Abigail E.; Migliano, Andrea B.; Dyble, Mark; Major-Smith, Daniel; Viguier, Sylvain; Hassan, Anushé
Abstract : Women cooperate over multiple domains and while research from western contexts portrays women's networks as limited in size and breadth, women receive help, particularly with childcare, from a diverse range of individuals (allomothers). Nonetheless, little exploration has occurred into why we see such diversity. Wide maternal childcare networks may be a consequence of a lack of resource accumulation in mobile hunter–gatherers—where instead households rely on risk-pooling in informal insurance networks. By contrast, when households settle and accumulate resources, they are able to retain risk by absorbing losses. Thus, the size and composition of mothers' childcare networks may depend on risk-buffering, as captured by mobile and settled households in the Agta, a Philippine foraging population with diverse lifestyles. Across 78 children, we find that childcare from grandmothers and sisters was higher in settled camps, while childcare from male kin was lower, offering little support for risk-buffering. Nonetheless, girls' workloads were increased in settled camps while grandmothers had fewer dependent children, increasing their availability. These results point to gender-specific changes associated with shifting demographics as camps become larger and more settled. Evidently, women's social networks, rather than being constrained by biology, are responsive to the changing socioecological context. This article is part of the theme issue 'Cooperation among women: evolutionary and cross-cultural perspectives'.